Prognostic Value of Abdominal Aortic Calcification: A Systematic Review and Meta‐Analysis of Observational Studies - Leow, Kevin (J Am Heart Assoc, 2021)
BACKGROUND: The prognostic importance of abdominal aortic calcification (AAC) viewed on noninvasive imaging modalities remains uncertain. METHODS AND RESULTS: We searched electronic databases (MEDLINE and Embase) until March 2018. Multiple reviewers identified prospective studies reporting AAC and incident cardiovascular events or all‐cause mortality. Two independent reviewers assessed eligibility and risk of bias and extracted data. Summary risk ratios (RRs) were estimated using random‐effects models comparing the higher AAC groups combined (any or more advanced AAC) to the lowest reported AAC group. We identified 52 studies (46 cohorts, 36 092 participants); only studies of patients with chronic kidney disease (57%) and the general older‐elderly (median, 68 years; range, 60–80 years) populations (26%) had sufficient data to meta‐analyze. People with any or more advanced AAC had higher risk of cardiovascular events (RR, 1.83; 95% CI, 1.40–2.39), fatal cardiovascular events (RR, 1.85; 95% CI, 1.44–2.39), and all‐cause mortality (RR, 1.98; 95% CI, 1.55–2.53). Patients with chronic kidney disease with any or more advanced AAC had a higher risk of cardiovascular events (RR, 3.47; 95% CI, 2.21–5.45), fatal cardiovascular events (RR, 3.68; 95% CI, 2.32–5.84), and all‐cause mortality (RR, 2.40; 95% CI, 1.95–2.97). CONCLUSIONS: Higher‐risk populations, such as the elderly and those with chronic kidney disease with AAC have substantially greater risk of future cardiovascular events and poorer prognosis. Providing information on AAC may help clinicians understand and manage patients' cardiovascular risk better.